2017
DOI: 10.1016/j.ttbdis.2017.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Molecular surveillance of Theileria parasites of livestock in Oman

Abstract: 10 Background 11Theileriosis is one of the most prevalent infectious diseases of livestock in the Arabian 12 Peninsula, and causes high rates of mortality and morbidity in sheep and cattle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
18
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 39 publications
6
18
1
Order By: Relevance
“…Thus, a mixture of both species was detected in the majority of blood samples. The lower prevalence of single T. ovis differs from an earlier survey in Oman, (April and August 2014) when single T. ovis infection was more dominant than single T. lestoquardi 6 . The lower prevalence of single T. ovis among the present cohort is unlikely to be due to technical deficiency generating false negative results, as the limit of detection of the T. ovis specific qPCR assay was two-fold higher than that of T. lestoquardi.…”
Section: Analysis Of T Lestoquardi and T Ovis Infected Sheep Fiftycontrasting
confidence: 86%
“…Thus, a mixture of both species was detected in the majority of blood samples. The lower prevalence of single T. ovis differs from an earlier survey in Oman, (April and August 2014) when single T. ovis infection was more dominant than single T. lestoquardi 6 . The lower prevalence of single T. ovis among the present cohort is unlikely to be due to technical deficiency generating false negative results, as the limit of detection of the T. ovis specific qPCR assay was two-fold higher than that of T. lestoquardi.…”
Section: Analysis Of T Lestoquardi and T Ovis Infected Sheep Fiftycontrasting
confidence: 86%
“…They found that T. annulata infection was more prevalent in indigenous animals. The molecular techniques are more effective in detecting T. annulata infection and have higher specificity in comparison with other techniques [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tick-borne diseases of cattle such as theileriosis and babesiosis are important due to the losses they cause to animal health and industries (2). These diseases record high presence in the Arabian Gulf regions and place severe impact on their economies (3). Ticks can be transmitted and spread out by various ways including but not limited to moving of animals from an area to another searching for food and water.…”
Section: Introductionmentioning
confidence: 99%